Randomised, quadruple blinded, placebo controlled, multicentre trial investigating prophylactic tamsulosin in prevention of postoperative urinary retention in men after endoscopic total extraperitoneal inguinal hernia repair (STOP-POUR trial): a study protocol - Nicole Graf; Antonio Nocito; Gerfried Teufelberger; Marco Bieri; Uwe Bieri; Juliette Slieker; Lukas John Hefermehl; Sebastian Soppe; Regula Tedaldi (BMJ Open)
Introduction Postoperative urinary retention (POUR) is a common complication after inguinal hernia repair with a reported incidence up to 34%. It can be described as the inability to initiate urination or insufficient bladder emptying following surgery. It usually requires the use of catheterisation to empty the bladder in order to prevent further injury to the bladder or kidneys and to relief from pain. Tamsulosin is a medication that is commonly used in men with urinary symptoms related to an enlarged prostate. There is some evidence to suggest that it may also potentially be beneficial for preventing POUR.Methods and analysis This is a multicentre, blinded, prospective, phase IV randomised controlled trial with parallel allocation. Six hundred and thirty-four patients scheduled for elective endoscopic inguinal hernia repair surgery will be recruited. There will be effective (concealed) randomisation of the subjects to the intervention/control groups. Group assignment will be performed using a covariate-adaptive allocation procedure to provide a balance for selected covariates. The interventional group receives 0.4 mg tamsulosin hydrochloride and the control-group receives one placebo capsule matching the active study drug, both daily, starting from 5 days prior to the day of surgery, at the day of surgery and for 1 day following surgery. The primary outcome is any need for urinary catheterisation postoperatively as a binary outcome. Secondary outcome measures include postoperative pain, change in International Prostate Symptom Score from baseline prior to surgery to after surgery and hospital stay.Ethics and dissemination The study has been approved by the Northwestern and Central Switzerland Ethics Committee (2020–00569) and it is being conducted in accordance with the Declaration of Helsinki and Good Clinical Practice. Study results will be disseminated through peer-reviewed journals and national and international scientific conferences.Trial registration numbers SNCTP000003904. NCT04491526.